Monitoring Cloud Motion in Cyprus for Solar Irradiance Prediction - Charalambides, Alexandros G.; Tapakis, Rogiros (My University, 2013)
Solar Energy is the feedstock for various applications of renewable energy sources; thus, the knowledge of the intensity of the incident solar irradiance is essential for monitoring the performance of such systems. The major unpredictable factor in defining the solar irradiance and the performance of solar systems is the presence of clouds in the sky. So far, various researchers proposed several models to correlate solar irradiance to cloud coverage and cloud type. The present work describes the development of a simple method for cloud detection and computation of short-term cloud motion. The minimum accuracy of the model was 95% for the prediction of the cloud location seven timesteps in advance with only three cloud images processed. When including the dimensions of the cloud to the accuracy calculation, the minimum accuracy was 88%.
Keywords: Solar Energy; Solar Irradiance Prediction; Monitoring Cloud Motion